EFEKTIVITAS MODEL PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI SEKOLAH MENENGAH KEJURUAN NEGERI 1 SIANTAR - Muhammad Ali Hanafiah; Ahmad Syafri; Maya Ardina Hasibuan; Fhany Wardhana Salamony; Ahmad Fuadi Fauzi (Yayasan Pendidikan Islam dan Multikultural, 2021)
Abstract: The Covid-19 pandemic has had such a significant impact on the educational aspect of the current era of disruption, hence the emergence of causes in various changes, especially in the strategies and teaching methods carried out by teachers. The online learning method is a learning method carried out during a pandemic in accordance with regulations. The purpose of this research is to describe the effectiveness of online learning models during the COVID-19 pandemic. This type of research is a quantitative research with a non-equivalent control group design research model of experimental design (quasi-experiment). The subjects in this study were SMK Negeri 1 Siantar. Various populations in the research conducted were students of class X with a total of 68 people. The data analysis technique is through the Normality-Gain Test N Gain dan T-Test in both sample groups. The N-gain value in the experimental class was 53.77%, while the control class had the N-gain value of 59.30%. Based on the results of the T-test there are significant differences between student learning outcomes with synchronous learning methods and asynchronous learning methods. The level of effectiveness occurs in the synchronous method using video conferencing, so that the implementation of the synchronous method can improve student learning outcomes.